Complications of hypospadias surgery: Experience in a tertiary hospital of a developing country. - Appeadu-Mensah, W.; Hesse, A.A.J.; Glover-Addy, H.; Osei-Nketiah, S.; Etwire, V.; Sarpong, P. (Afr J Paediatr Surg., 2015)
Background: Over 300 different operations have been described for the management of hypospadias. In recent times, the numbers of operations used in various centres have gradually reduced as the principles necessary to ensure adequate cosmetic and functional results with minimum complications are better understood. The aim of this article was to review the different types of operations used for managing hypospadias in a tertiary hospital in a developing country, to analyse the complications of surgery and discuss the factors that contribute to complications. Materials and Methods: Patient folders, theatre, and ward records were used to obtain the required information. The age at surgery, types of hypospadias at presentation, types of operations done and complications were analysed. Results and Conclusion: With three main types of operations, tubularised incised plate urethroplasty and meatal advancement and glanuloplasty incorporated for anterior hypospadias (glanular, coronal, subcoronal, distal, midpenile), and lateral based flap urethroplasty for posterior hypospadias (proximal penile, penoscrotal, scrotal, perineal), most hypospadias were corrected with acceptable complication rates.
Keywords: Complications; hypospadias surgery; lateral based flap urethroplasty; tubularised incised plate urethroplasty